Analysis of the Measurement Properties of the Female Sexual Function Index 6-item Version (FSFI-6) in a Postpartum Brazilian Population - Julianna de Azevedo Guendler; Melania Maria Amorim; Maria Eduarda Melo Flamini; Alexandre Delgado; Andrea Lemos; Leila Katz (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
Abstract Objective We evaluated internal consistency, test-retest reliability, and criterion validity of the Brazilian Portuguese version of the Female Sexual Function Index 6-item Version (FSFI-6) for postpartum women. Methods Therefore, questionnaires were applied to 100 sexually active women in the postpartum period. The Cronbach α coefficient was used to evaluate the internal consistency. Test-retest reliability was analyzed by Kappa for each item of the questionnaire and by the Wilcoxon parametric test, comparing the total scores of each evaluation. For the assessment of criterion validity, the FSFI was used as the gold standard and the receiver operating characteristic (ROC) curve was constructed. Statistical analysis was performed using IBM SPSS Statistics for Windows, version 21.0 (IBM Corp., Armonk, NY, USA). It was found that the internal consistency of the FSFI-6 questionnaire was considerably high (0.839). Results The test-retest reliability results were satisfactory. It can also be stated that the FSFI-6 questionnaire presented excellent discriminant validity (area under the curve [AUC] = 0.926). Women may be considered as having sexual dysfunction if the overall FSFI-6 score is < 21, with 85.5% sensitivity, 82.2% specificity, positive likelihood ratio of 4.81 and negative likelihood ratio of 0.18. Conclusion We conclude that the Brazilian Portuguese version of FSFI-6 is valid for use in postpartum women.